2021
DOI: 10.3390/ma14133565
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Thermal Aging Effect on the Properties of Silicone-Based and Silicone-Free Thermal Gap Filler Materials

Abstract: Thermal conductive gap filler materials are used as thermal interface materials (TIMs) in electronic devices due their numerous advantages, such as higher thermal conductivity, ease of use, and conformity. Silicone is a class of synthetic materials based on a polymeric siloxane backbone which is widely used in thermal gap filler materials. In electronic packages, silicone-based thermal gap filler materials are widely used in industries, whereas silicone-free thermal gap filler materials are emerging as new alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…In recent years, improving the light output e ciency and high dynamic display performance of devices by introducing functional structures during the LED packaging manufacturing process has become a research hotspot [8]. However, common LED packaging materials such as silicone resin have the drawbacks of high elasticity, low hardness, and poor workability at room temperature, which are important reasons for the di culty in manufacturing microstructures on the LED packaging surface [9], [10]. In traditional processing, soft elastic materials have increasingly serious problems, such as low processing accuracy and poor surface processing quality as the processing size decreases, a signi cant factor hindering the development of micro-LED devices.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, improving the light output e ciency and high dynamic display performance of devices by introducing functional structures during the LED packaging manufacturing process has become a research hotspot [8]. However, common LED packaging materials such as silicone resin have the drawbacks of high elasticity, low hardness, and poor workability at room temperature, which are important reasons for the di culty in manufacturing microstructures on the LED packaging surface [9], [10]. In traditional processing, soft elastic materials have increasingly serious problems, such as low processing accuracy and poor surface processing quality as the processing size decreases, a signi cant factor hindering the development of micro-LED devices.…”
Section: Introductionmentioning
confidence: 99%
“…Kashi et al [21] observed a decrease in both the tensile strength and the elongation at break for silicone rubber after accelerated aging in oil. Regarding the aging conditions specific to high-performance electronics, some previous works exist [22,23], but many subjects are yet to be addressed, specially in the context of aging in hermetic environments.…”
mentioning
confidence: 99%